PENCEGAHAN PERBURUKAN PADA PENYAKIT PARKINSON: PENDEKATAN FARMAKOLOGIS DAN NON-FARMAKOLOGIS - Subagya; Rohma, Novita Nur; Gofir, Abdul; Ar Rochmah, Mawaddah (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
Parkinson's disease (PD) is a complex neurodegenerative disorder with a progressive course. Most patients experience symptom deterioration over time, although the rate of progression varies between individuals. PD is the second most common neurodegenerative disease worldwide, with prevalence exceeding ~1% in people over 60 and ~5% in those over 85. Its incidence is rising globally with aging populations, and the number of PD cases is projected to double by 2040 compared to 2015. Despite significant advances in symptomatic treatments, no intervention has been proven to halt or reverse the underlying pathology of PD. This therapeutic gap underscores the importance of strategies aimed at preventing disease progression in order to preserve functional capacity and improve patients’ quality of life. This review provides an overview of the progressive nature of PD, current challenges in its management, and both pharmacological and non-pharmacological approaches aimed at preventing further deterioration. Keywords: Prevention, Parkinson’s disease, progressive, neurodegenerative